Suction effects on bridge pier scour - Goh, Edwin Kok Wei. (2009)
This experimental study aims to investigate how suction affects local scour around bridge pier in a clear-water flow. Traditional methods to counter the scour phenomenon often induce secondary failure mechanisms. As such, utilization of suction as a countermeasure will not only eliminate such mechanisms but also reduce the scouring effect. In this study, the flow depth was kept constant at 105 mm, and the suction rate was maintained at 0.35 liter/sec. The diameter of the modeled pier is 75 mm and the suction location varies at different location downstream of the pier. The empirical data showed that suction has an effect on the development of pier-scour under a clear-water channel condition. The data also show that the scour depth can be reduced by as much as 48% with the help of suction. It was also observed that the reduction on scour is dependent on the location of the source of suction. There is also an unexpected secondary peak when the suction effect is located at x/D = -10.